2004
DOI: 10.1099/mic.0.27224-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bacteriophage ϕEa1h lysozyme in Escherichia coli and its activity in growth inhibition of Erwinia amylovora

Abstract: A 3·3 kb fragment from Erwinia amylovora phage ϕEa1h in plasmid pJH94 was previously characterized and found to contain an exopolysaccharide depolymerase (dpo) gene and two additional ORFs encoding 178 and 119 amino acids. ORF178 (lyz) and ORF119 (hol) were found to overlap by 19 bp and they resembled genes encoding lysozymes and holins. In nucleotide sequence alignments, lyz had structurally conserved regions with residues important for lysozyme function. The lyz gene was cloned into an expression vector and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
1
19
1
1
Order By: Relevance
“…116 The theory that removing the bacterial EPS can reduce the pathogen's ability to colonize and cause disease was tested by removing the EPS layer of the plant pathogen Erwinia amylovora. 123,124 Erwinia spp. phage depolymerase DpoEa1h, efficiently degrades the major EPS component amylovoan of the E. amylovora capsule.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
See 1 more Smart Citation
“…116 The theory that removing the bacterial EPS can reduce the pathogen's ability to colonize and cause disease was tested by removing the EPS layer of the plant pathogen Erwinia amylovora. 123,124 Erwinia spp. phage depolymerase DpoEa1h, efficiently degrades the major EPS component amylovoan of the E. amylovora capsule.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
“…125 Expression of DpoEa1h in transgenic apple and pear plants significantly reduced fire blight (E. amylovora) susceptibility, 124 likely due to removal of the main virulence factor amylovoran and exposing the cells to host plant defenses. 123 Polysaccharide capsule is also an important virulence factor for Klebsiella pneumoniae, contributing to its resistance to antibiotics. A depolymerase encoded by Aeromonas punctata was capable of degrading capsular EPS of K. pneumoniae, which reinstated sensitivity to gentamicin.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
“…At present, control of E. amylovora with bacteriophages is under investigation mainly in Canada and in the United States of America. Studies in Europe are currently limited to only a few countries with a primary focus on the morphology, molecular characterization, and host range studies of E. amylovora phages and examination of phage efficacy during in vitro conditions [61,67,[74][75][76][77]. Apart from some exceptions, these investigations do not report any field experiments with these phages.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Since the 1970s, more and more phages have been isolated and subsequently characterized in detail [54][55][56][57][58][59][60][61]. However, until recently, numerous efforts to control fire blight in orchards failed because phage populations declined in the absence of E. amylovora [23,56,58].…”
Section: Phages Combined With Other Microorganisms or Applied As Phagmentioning
confidence: 99%
“…It was shown that when recombinant lysozyme of Erwinia amylovora phage Ea1h was applied on immature pears after inoculation with E. amylovora, disease symptoms such as ooze formation and necrosis were retarded or inhibited (Kim et al 2004). Alternatively, transgenic plants able to produce lysin enzyme at the intercellular spaces of the plant to kill bacteria at a very early stage of infection could be developed (During et al 1993).…”
Section: Application Of Phage Lysin In Foodmentioning
confidence: 99%